Heritability of Blood Pressure in an Iranian Population - M Saadat; M Sadeqi; DD Farhud; A Bahaoddini (Tehran University of Medical Sciences, 2001)
The fact that life styles and personal interests, aggregate within families suggests that shared environment in addition to shared bioligical factors could play a role in determining the phenotypic similarity of idividuals living in the same household. It is a major concern of cardiovascular epidemiologists to know how much of the familial aggregation of blood pressure is attributable to shared genes and/or shared family environment. Genetic and environmental influences on blood pressure was examined in a sample representative of the adult population of Shiraz, Fars province, south of Iran. The studied population was the 107 pairs of mother and dauther. Analysis of the data suggest that the genetic heritabilities were estimated to be 0.58,0.30, 0.60 for systolic, diastolic, and mean blood pressure, respectively.